Literature Review: The Potential of Soft Coral Lobophytum sp. as a Source of Pharmaceutical Ingredients - Purnomo, Indra; Lisnasari, Baiq Risky Wahyu; Ulya, Tuhfatul; Maulidya, Selvira Anandia Intan; Budastra, Wayan Cintya Ganes (Jurnal Biologi Tropis, 2026)
Lobophytum sp. is a soft coral found in Indonesian waters, mainly distributed on coral reef slopes. Lobophytum sp. contains various terpenoid compounds, including sesquiterpenes and terpenoid glycosides, which have a variety of biological activities. This literature review examines the pharmacological potential of Lobophytum sp. based on ten studies reporting its pharmacological activities, such as antibacterial, antimicrobial, hepatoprotective, anti-arthritic, antioxidant, anti-inflammatory, antimalarial, and neuroprotective properties. The diterpene cembranoids in Lobophytum sp. show potential as candidate active substances for the development of pharmaceutical products through various in vitro and in vivo studies. The antioxidant activity of cembranoids has the potential to be developed as an anti-aging agent. In addition, its anti-inflammatory, antibacterial, and cytotoxic activities can be developed in the form of topical preparations. However, the development of Lobophytum sp. As a source of active ingredients still faces various challenges, especially the limited isolation of cembranoids, which requires a biotechnological approach.